2006
DOI: 10.1542/peds.2006-0424
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 4 Genes Between Chromosome 15 Breakpoints 1 and 2 and Behavioral Outcomes in Prader-Willi Syndrome

Abstract: Prader-Willi syndrome is a neurodevelopmental disorder that is characterized by infantile hypotonia, feeding difficulties, hypogonadism, mental deficiency, hyperphagia (leading to obesity in early childhood), learning problems, and behavioral difficulties. A paternal 15q11-q13 deletion is found in ~70% of patients with Prader-Willi syndrome, ~25% have uniparental maternal disomy 15, and the remaining 2% to 5% have imprinting defects. The proximal deletion breakpoint in the 15q11-q13 region occurs at 1 of 2 sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 26 publications
2
85
0
Order By: Relevance
“…We previously reported the first association of larger deletion size in PWS and poorer clinical outcomes [Butler et al, 2004] and described an association between expression levels of the four reported genes between BP1 and BP2 and aberrant behavior [Bittel et al, 2006]. Our aCGH analysis also shows larger deletions than previously identified with more variation in size.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We previously reported the first association of larger deletion size in PWS and poorer clinical outcomes [Butler et al, 2004] and described an association between expression levels of the four reported genes between BP1 and BP2 and aberrant behavior [Bittel et al, 2006]. Our aCGH analysis also shows larger deletions than previously identified with more variation in size.…”
Section: Discussionsupporting
confidence: 65%
“…Several copy number variants outside the Prader-Willi chromosome region (e.g., 3q, 8p) were confirmed using quantitative PCR with primers specific to the region of interest (i.e., deleted or duplicated) and compared to CNVs reported in the human genome (see http://projects.tcag.ca/variation/). Equal quantities of genomic DNA from PWS subjects and chromosomally normal comparison subjects were added to a hot-start quantitative PCR mix including SYBR green (Invitrogen, Inc., Carlsbad, CA) and PCR performed in an ABI 7000 thermocycler according to the manufacturer's instructions as previously described [Bittel et al, 2006[Bittel et al, , 2007b. Five replicates of each sample were run.…”
Section: Methodsmentioning
confidence: 99%
“…The use of gene expression data will increase as sample sizes grow, as additional molecularly defined syndromes are characterized by expression arrays 37,44 and as expression information is better integrated with comprehensive phenotypic data 81 . It is also likely that the integration of expression studies with high-density SNP arrays will ultimately come to elucidate how disease-associated variants affect cellular function 82 .…”
Section: Array Analyses -From Genes To Pathwaysmentioning
confidence: 99%
“…Cyfip1 and Cyfip2 are members of a highly conserved gene family 52 , and dysregulation of Cyfip1 expression levels leads to pathological changes in neuronal maturation and connectivity, both of which may contribute to the development of the neurological symptoms observed in ASD and schizophrenia 63 . A CNV in the 15q11.2 region of the human genome has been implicated in several neurological and neuropsychiatric conditions [64][65][66][67][68][69][70] and a CYFIP1 CNV within 15q11.2 has been linked to ASD 71 , with an upregulation of CYFIP1 mRNA being demonstrated in genomewide expression profiling of ASD patients with 15q11-q13 duplication 72 . A rare CYFIP1 deletion has also been reported in a patient with a mild intellectual disability and a pervasive developmental disorder not otherwise specified 71 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%